The relationship between entrepreneurial orientation and organizational innovation: Empirical evidence from Malaysian SMEs - Zakaria, Nazlina; Chew Abdullah, Nor Azimah; Yusoff, Rushami Zien (Society for Business Research Promotion, 2015)
Previous research found that organization which have a more innovative behavior are likely to initiate an organizational change that could affect organizational performance. In this study, entrepreneurial orientation is considered as the spark that stimulates the innovation activities in SMEs.The aim of this study is to investigate the relationship between entrepreneurial orientation and organizational innovation in Malaysian SMEs. Therefore, this article discusses the concept of organizational innovation, entrepreneurial orientation and end with the findings of the relationship between entrepreneurial orientation and organizational innovation.Data was collected from SMEs in manufacturing sectors.A total of 321 self-administered questionnaires were analyzed using Smart PLS 2.0. The results reveal a positive relationship between entrepreneurial orientation and organizational innovation.Hence, this study is useful for future researchers, entrepreneurs and policy makers in realizing the importance of entrepreneurial orientation in promoting organizational innovation.